Novel anionic polymethines of the fluorene series - Kurdyukova, I.V.; Ishchenko, A.A.; Mysyk, D.D. (Reports of the National Academy of Sciences of Ukraine, 2017)
The vinylogical series of anionic polymethine dyes based on tris(2,2,3,3,4,4,5,5-octafluoropenthyl)-9H-fluorene-2,4,7-trisulfonate is synthesized. It is shown that, in contrast to similar derivatives of polynitrofluorene, the most intense and long-wavelength electronic transition is the polymethine transition. It is found that the absorption band of this transition for highest vinylogies, in contrast to those of classic polymethines, is preserved very intense and narrow even in highly polar solvents.